Single-cell RNA-seq analysis reveals dual sensing of HIV-1 in blood Axl+ dendritic cells - Flavien Brouiller; Francesca Nadalin; Pierre-Emmanuel Bonté; Ouardia Ait-Mohamed; Constance Delaugerre; Jean-Daniel Lelièvre; Florent Ginhoux; Nicolas Ruffin; Philippe Benaroch (iScience, 2023)
Summary: Sensing of incoming viruses is a pivotal task of dendritic cells (DCs). Human primary blood DCs encompass various subsets that are diverse in their susceptibility and response to HIV-1. The recent identification of the blood Axl+DC subset, endowed with unique capacities to bind, replicate, and transmit HIV-1 prompted us to evaluate its anti-viral response. We demonstrate that HIV-1 induced two main broad and intense transcriptional programs in different Axl+DCs potentially induced by different sensors; an NF-κB-mediated program that led to DC maturation and efficient CD4+ T cell activation, and a program mediated by STAT1/2 that activated type I IFN and ISG responses. These responses were absent from cDC2 exposed to HIV-1 except when viral replication was allowed. Finally, Axl+DCs actively replicating HIV-1 identified by quantification of viral transcripts exhibited a mixed NF-κB/ISG innate response. Our results suggest that the route of HIV-1 entry may dictate different innate sensing pathways by DCs.